2014
DOI: 10.1111/iju.12610
|View full text |Cite
|
Sign up to set email alerts
|

Association of urinary incontinence and sexual function in women

Abstract: Abbreviations & AcronymsObjectives: To investigate the association between urinary incontinence and female sexual function in a non-clinical population. Methods: A self-administered questionnaire was distributed to 2159 female employees of two hospitals. Results: Of the 883 sexually active participants, pure stress urinary incontinence was reported in 18.3%, pure urge urinary incontinence in 6.8%, mixed urinary incontinence in 15.1% and no urinary incontinence in 59.8%. The prevalence of female sexual difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 28 publications
1
22
0
3
Order By: Relevance
“…These symptoms are often associated; 25% of patients consulting for genitourinary prolapse also suffer terminal constipation, and 33% from anal incontinence . They can cause functional difficulties beyond the organ concerned, for example, urinary incontinence affects sexual satisfaction . Studies have demonstrated that treatment for one symptom can improve, worsen, or even predispose another .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These symptoms are often associated; 25% of patients consulting for genitourinary prolapse also suffer terminal constipation, and 33% from anal incontinence . They can cause functional difficulties beyond the organ concerned, for example, urinary incontinence affects sexual satisfaction . Studies have demonstrated that treatment for one symptom can improve, worsen, or even predispose another .…”
Section: Introductionmentioning
confidence: 99%
“…3 They can cause functional difficulties beyond the organ concerned, for example, urinary incontinence affects sexual satisfaction. 4 Studies have demonstrated that treatment for one symptom can improve, worsen, or even predispose another. 5 Epidemiologists as clinicians need tools to assess the prevalence of symptoms associated with functional PFD and the severity of these symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Women with mixed UI had the worst sexual function . Concerning the effect of UI on individual domains of female sexual function, while all types of UI increased the risk for FSD by 1.6‐fold to 1.8‐fold, pure Urgency UI was a risk factor for decreased lubrication and increased coital pain while mixed UI was associated with less sexual satisfaction …”
Section: Introductionmentioning
confidence: 97%
“…Women who experience UUI are also less likely to be sexually active than overactive bladder (OAB) dry woman and women without OAB [6••]. Women with severe urinary incontinence are significantly more likely to experience diminished libido (OR 1.96), vaginal dryness (OR 2.11), and dyspareunia (OR 2.04) independent of age, educational level, and race [7,8].…”
Section: Introductionmentioning
confidence: 99%